2005
DOI: 10.1580/pr04-04.1
|View full text |Cite
|
Sign up to set email alerts
|

Tibetans at Extreme Altitude

Abstract: Between 1960 and 2003, 13 Chinese expeditions successfully reached the summit of Chomolungma (Mt Everest or Sagarmatha). Forty-five of the 80 summiteers were Tibetan highlanders. During these and other high-altitude expeditions in Tibet, a series of medical and physiological investigations were carried out on the Tibetan mountaineers. The results suggest that these individuals are better adapted to high altitude and that, at altitude, they have a greater physical capacity than Han (ethnic Chinese) lowland newc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Tibetans show greater adaptability to the hypoxic environment of high-altitude regions compared to people belonging to the Han ethnicity; the incidence of HAPE was significantly less in Tibetans compared to that observed in people belonging the Han ethnicity (Cheng et al, 1997;Basu et al, 2007). Genetic factors accounted for approximately 50% of the factors influencing the adaptation of the human body to highaltitude hypoxic environments (Wu et al, 2005;Wu and Kayser, 2006). In this study, 10 susceptibility genes related to HAPE were identified/screened from the NCBI database; these genes coded for aldosterone synthase 2 (CYP11B2), ACE, heat-shock protein-70 (HSP70), nuclear factor-kappa B (NF-κB), SP-A2, NOS,VEGF,prolyl hydroxylase (EGLN1), and the zinc finger protein A20.…”
Section: Discussionmentioning
confidence: 95%
“…Tibetans show greater adaptability to the hypoxic environment of high-altitude regions compared to people belonging to the Han ethnicity; the incidence of HAPE was significantly less in Tibetans compared to that observed in people belonging the Han ethnicity (Cheng et al, 1997;Basu et al, 2007). Genetic factors accounted for approximately 50% of the factors influencing the adaptation of the human body to highaltitude hypoxic environments (Wu et al, 2005;Wu and Kayser, 2006). In this study, 10 susceptibility genes related to HAPE were identified/screened from the NCBI database; these genes coded for aldosterone synthase 2 (CYP11B2), ACE, heat-shock protein-70 (HSP70), nuclear factor-kappa B (NF-κB), SP-A2, NOS,VEGF,prolyl hydroxylase (EGLN1), and the zinc finger protein A20.…”
Section: Discussionmentioning
confidence: 95%
“…Everest in 1975, the 9 summiteers were all Tibetans, except for one Han. On this expedition the climbers placed a trigonometric survey tripod on the summit that required drilling holes in the rock, and this heavy work was carried out for more than an hour without supplementary oxygen (Wu et al, 2005b). Today, Sherpas summit Mt.…”
Section: Physical Performancementioning
confidence: 99%
“…Highlander population has developed different adaptive strategies for coping with highaltitude environment [10,11]. Lower frequency of AMS is reported from Tibetans [84,85]. In a study on Andean Quechua, G allele at the G894T polymorphism in NOS3, suggested to be beneficial in hypoxic environments, was more frequent compared to lowland Amerindians [80], while the frequency of the same allele was low in Nepalese population who suffered from AMS [79].…”
Section: Genetic Basis For Altitude Illnessmentioning
confidence: 99%